Handshake Stewardship: A Highly Effective Rounding-based Antimicrobial Optimization Service. Issue 10 (October 2016) - Hurst, Amanda L.; Child, Jason; Pearce, Kelly; Palmer, Claire; Todd, James K.; Parker, Sarah K.
Abstract : Background: Implementation of an antimicrobial stewardship program is recommended as one solution to combat increasing antimicrobial resistance. Most antimicrobial stewardship programs use preauthorization or restrictive strategies recommended in national guidelines. We describe a unique, rounding-based strategy, handshake stewardship. Handshake stewardship is distinguished by: (1) lack of restriction and preauthorization, (2) review of all prescribed antimicrobials and (3) a rounding-based, in-person approach to feedback by a pharmacist–physician team. Methods: We retrospectively measured antimicrobial use hospital-wide and by unit during preimplementation, planning, and postimplementation phases of the handshake stewardship approach to determine the efficacy of this strategy in decreasing use in a freestanding children's hospital. All antimicrobials prescribed on the inpatient services between October 2010 and September 2014 were included in the review. Monthly antimicrobial use (hospital-wide and by unit) was measured in days of therapy per 1000 patient days (DOT/1000 PD). Results: Overall antimicrobial use decreased by 10.9% during the 4 years of the analysis (942 to 839 DOT/1000 PD, P < 0.01), with an impact of 10.3% on antibacterials (750 to 673 DOT/1000 PD, P < 0.01). Vancomycin use decreased by 25.7% (105 to 78 DOT/1000 PD, P < 0.01). Meropenem use decreased by 22.2% (45 to 35 DOT/1000 PD, P = 0.04) without a compensatory increase of other antipseudomonal agents. Decreased usage was observed both hospital-wide and on individual units for most agents. Conclusions: The handshake stewardship approach is an effective strategy for an antimicrobial stewardship program, as demonstrated by the widespread and significant decrease in antimicrobial use after implementation. Abstract : Supplemental Digital Content is available in the text.